2020
DOI: 10.1039/c9cp07007a
|View full text |Cite
|
Sign up to set email alerts
|

On the development of a gold-standard potential energy surface for the OH + CH3I reaction

Abstract: We develop the first accurate full-dimensional ab initio PES for the OH− + CH3I SN2 and proton-transfer reactions treating the failure of CCSD(T) at certain geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 36 publications
1
56
0
1
Order By: Relevance
“…For the development of the global analytical ab initio PES of the OH − + CH 3 F reaction the same procedure is utilized as in the case of the OH − + CH 3 I reaction described in ref. 35 . The PES development is performed with the R obosurfer program package at the MP2/aug-cc-pVDZ level of theory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the development of the global analytical ab initio PES of the OH − + CH 3 F reaction the same procedure is utilized as in the case of the OH − + CH 3 I reaction described in ref. 35 . The PES development is performed with the R obosurfer program package at the MP2/aug-cc-pVDZ level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…Our main goal is to take into account the effect of the deep post-reaction well on the title S N 2 reaction by computing nearly 1 million full-length quasi-classical trajectories (QCT) and considering a wide range of E coll . To perform these QCT computations, relying on our previous study, 35 we construct a global full-dimensional ab initio potential energy surface (PES) for the OH − + CH 3 F reaction utilizing the R obosurfer program package recently developed in our group. 36 Our dynamics simulations reveal a novel reaction route, observed at lower E coll , where a fluoride ion is substituted by an oxide ion leading to the HF + CH 3 O − products.…”
Section: Introductionmentioning
confidence: 99%
“…38 Recently, we developed full-dimensional analytical potential energy surfaces for the OH − + CH3I reaction with various ab initio methods. 39 It was found that at certain geometries of the potential energy surface the CCSD(T) energy breaks down resulting an increase of the rejected unphysical trajectories in quasi-classical trajectory simulations. This problem was solved by proposing a Brueckner-type CCSD(T)-based composite method.…”
Section: Introductionmentioning
confidence: 99%
“…This problem was solved by proposing a Brueckner-type CCSD(T)-based composite method. 39 An evident way to extend the complexity of the X − + CH3Y reactions is to replace CH3Y with CH3CH2Y. In these cases, E2 reaction can also occur competing with the SN2 reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CCSD(T) breaks down in certain regions of the PES for the OH − + CH 3 I reaction, resulting in unphysically large reaction cross sections. 38 MRCI calculations for such a system are too expensive and not affordable currently, and thus alternative approaches are needed. Even when CCSD(T) is generally amenable, convergence to the correct state can sometimes be difficult in the presence of low-lying excited states.…”
mentioning
confidence: 99%